The Implementation of Stay and Stray Method in Teaching Reading of Recount Text to the Eighth Graders of SMP Muhammadiyah 8 Tanggulangin - Faishol Hadi; Muhammad Affif Muzabid (STKIP AL HIKMAH SURABAYA, 2024)
This study aims to investigate the implementation stay and stray method in teaching reading of recount text to the eighth grade of SMP Muhammadiyah 8 Tanggulangin. The research method used in this study was descriptive qualitative. This study used observation, interview, ans questionnaire as the data collection technique. The instrument of observation sheet was used to get the data of the implementation of stay and stray, while the instrument of questionnaire and interview sheet were used to get the data of students’ responses toward the implementation of stay and stray in learning reading. The subjects of this study were the English teacher and sixteen students of eighth grade of SMP Muhammadiyah 8 Tanggulangin. The result of this study showed that The teacher had implemented stay and stray in teaching reading of recount text precisely based on the syntaxes of the method itself. The steps which the teacher had used were asking the students to make a group and determining the stayers and strayers in each group, discussing a text in a group, asking strayers to get information from stayers of other groups, and presenting the information got. The study also showed that 75% students agreed that this method successfully helped them to be more active reading class. From their response, it could also be concluded that this method was able to make them more curious in understanding the text they read. 75% students also said that the group activity of this method help them to understand the text easily.